The in vitro effects of acidemia and acidemia reversal on coagulation in dogs - Kim, Youngju; Bae, Hyeona; Yu, DoHyeon (Frontiers in Veterinary Science, 2024)
BackgroundThe effect of acidemia on blood coagulation remains inadequately understood in veterinary medicine. Therefore, we assessed the effect of in vitro acidification of canine whole blood on coagulation and investigated whether acidemia-induced coagulopathy could be reversed by reversing acidemia.MethodsCitrated whole blood samples were taken from six healthy Beagle dogs and categorized, based on pH adjustment, into neutral, weak acidemia (WA), strong acidemia (SA), and reversal from SA. Then, prothrombin time (PT), activated partial thromboplastin time (aPTT), fibrinogen concentration, conventional thromboelastography (TEG) parameters, and velocity curve (V-curve) variables of TEG were assessed.ResultsThe PT, aPTT, and most TEG parameters showed significant coagulopathy in the SA group compared to the neutral group, with additional significant changes in reaction time (R), clot kinetic (K), maximum amplitude (MA), split point (SP), elasticity (E), thrombodynamic potential index (TPI), and coagulation index (CI) between the SA and WA groups. Among V-curve variables, the maximum rate of thrombus generation (MRTG) and total thrombus generation were significantly inhibited in the SA group compared to the neutral group, with significant differences in the time to maximum rate of thrombus generation (TMRTG) between the WA and SA groups. In the reverse group, aPTT, R, K, α-angle, MRTG, TMRTG, SP, TPI, and CI exhibited significant recovery compared to the SA group.ConclusionThe in vitro induction of acidemia in canine whole blood leads to impairment of coagulation profiles, and pH correction can reverse most acidemia-induced coagulopathy.